Strategi Gabungan Kelompok Tani Dalam Memberdayakan Petani Di Sekitar Area Pertambangan Batu Bara - Suma, Nasobi Niki; Chodijah, Siti Nurul (Al-I'timad: Jurnal Dakwah dan Pengembangan Masyarakat Islam, 2023)
Manunggal Jaya village is one of the food sheds that are in Kalimantan Timur. But as the age developed this village changed.This is a sign of the farming land that has begun to narrow. Irrigation was disrupted due to coal mining activities and communities exposed to waste from the mining. Farming land that began to shrink, irrigation disrupted due to coal mining activities and communities exposed to waste from the mining. As for the study's purpose: (1) to know the multi-use farm program in the middle of the coal mine, and (2) knew the combined strategy of farm groups to empower farmers in the middle of the coal mine area. This research uses descriptive qualitative methods through observation techniques, interviews and documentation. The results of research obtained by researchers in accordance with observation programs of empowerment cannot be felt by any farmer and are not carried out evenly because of minimal skills of agricultural and facility skills. The program implemented by the combined farming groups is the training of themes and materials organized according to existing agricultural potential, like giving the training of the stool dose according to the instructions, control of pests and diseases on plants, Home Food Training, and training system plant training line legowo. Whereas the combined strategy of the multi-purpose farming group is the development of human resources, The development of the group, The capital of the world is the, development of productive activities, and providing the right information for.